The Ontario Métis : characteristics and identity - Peters, Evelyn; Rosenberg, Mark; Halseth, Greg (Institute of Urban Studies, 1991)
Report: iv, 83 p., maps, digital file Questions about the nature of Métis identity have received considerable scrutiny in recent years (Foster, 1985; Hatt, 1971; Peterson and Brown, 1985). Events at Red River and Batoche have come to public attention in new ways, and this Prairie segment of Metis history has become increasingly well known. At the same time, it is evident that there are considerable populations in all parts of Canada which consider-themselves Metis, many of which do not have Red River ancestry (Table 1.0). This report explores the issue of Métis identity by analyzing the opinions and attitudes of an Ontario population which identifies itself as Métis, but appears to have few historic links with the Métis at Red River. The data derive from a 1985 questionnaire survey by the Ontario Métis and Non-Status Indian Association (OMNSIA). The survey attempted to identify the concerns, attitudes and opinions of OMNSIA members on issues of relevance to Metis and Non-Status Indians in Ontario (see Appendix A). While there are a number of problems with the survey, it nevertheless represents a unique and valuable resource for research ori Metis identity.